The TQE principal : a transformed leader - Sagor, Richard; Barnett, Bruce G. (Thousand Oaks, Calif. : Corwin Press, 1994)
This easy to read, practical book distills the key skills and techniques that principals need if they are to become effective TQE-based instructional leaders. The book includes useful charts, checklists, timelogs, key terms and concepts, references for future study and a planning and troubleshooting guide
Includes bibliographical references.
Keywords: Educational leadership -- United States; School management and organization; Total quality management -- United States; school management -- United States